Factors influencing malnutrition among adolescent girls in The Gambia: a mixed-methods exploratory study - Haddy Jallow-Badjan; Tanefa A. Apekey; Maria J. Maynard (BMC Public Health)
Abstract Background In The Gambia, existing research to understand and address malnutrition among adolescent girls is limited. Prior to the conduct of large-scale studies, formative research is needed. The aim of this mixed methods, cross-sectional study was to explore cultural contexts relevant to nutritional status, feasibility and appropriateness of recruitment and data collection methods (questionnaires and anthropometric measures), and plausibility of data collected. Methods The study took place in May–June 2021 in an urban conurbation in Brikama local government area (LGA) and two rural villages in Mansakonko LGA, The Gambia. The purposive sampling frame of the all-female sample included residence in the selected urban or rural settings and being aged 10–14 or 15–19 years. Thirty-two girls aged 10 to 19 years, with equal numbers in urban and rural settings were recruited. Four focus groups discussions (FGDs), with eight participants in each, were held to understand perspectives on cultural practices; concepts of under- and overweight, and research recruitment methods. The same participants completed questionnaires on socioeconomic circumstances, health, access to community resources, nutrition knowledge, sleep, and physical activity, and had anthropometric measures taken. FGDs were then reconvened to discuss the feasibility and acceptability of the questionnaires and anthropometric measures, and views on providing biological samples in the future. FGD data were analysed using thematic analysis. Body mass index (BMI)-for-age and height-for-age z-scores, mid-upper arm circumference, and waist: hip ratios were assessed and descriptive statistics used to explore the data obtained. Results Five themes were identified in the focus group discussions: 1. Cultural norms: harmful vs. beneficial to nutrition-related health; 2. Concepts of healthy diet and weight; 3. Approaches to tackling under- and overnutrition; 4. Study recruitment: barriers and facilitators; 5. Study questionnaires and proposed measures are mostly feasible and acceptable. Questionnaire data highlighted limited access to resources (e.g. food markets and electricity) as important individual, household and community factors influencing malnutrition in rural settings. The anthropometric measures reflected the double burden of malnutrition in The Gambia, with the presence of stunting (41%), underweight (31%), and living with overweight or obesity (10%). A higher proportion of participants were underweight in rural compared to urban settings (50% vs 12.5% respectively, p = 0.03). Over 70% of those classified as underweight perceived their weight as normal. Conclusion This exploratory study provides novel data to inform larger-scale research to understand and address malnutrition among adolescent females in The Gambia. Urban–rural variance in the double burden of malnutrition, factors influencing malnutrition, and in the barriers to and facilitators of adolescents taking part in research, are key considerations.